1986
DOI: 10.4992/psycholres1954.28.186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stimulus- or response-oriented training on psychophysiological responses and the propositional structure of imagery

Abstract: This research was performed to test Lang's theory (1979a) about psychophysiological changes accompanied with the emotional imagery. The purposes were to reconfirm his observation, and to investigate further the effects of response-and stimulus-oriented trainings on psychophysiological responses to various propositional structures of imagery when subjects were asked to imagine freely instead of using given imagery scripts. Twenty subjects were devided into stimulus and response groups. After a relaxation traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…First, individuals with good imagery ability are more likely to display a psychophysiological arousal pattern that follows imagery script content. Second, imagery scripts with an emphasis on response elements are superior to scripts containing mainly stimulus elements in eliciting a realistic psychophysiological response pattern (Hirota & Hirai, 1986;Lang et al, 1980). The use of personally relevant material in the script enhances the psychophysiological response of individuals (Pitman et al, 1987(Pitman et al, , 1990.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, individuals with good imagery ability are more likely to display a psychophysiological arousal pattern that follows imagery script content. Second, imagery scripts with an emphasis on response elements are superior to scripts containing mainly stimulus elements in eliciting a realistic psychophysiological response pattern (Hirota & Hirai, 1986;Lang et al, 1980). The use of personally relevant material in the script enhances the psychophysiological response of individuals (Pitman et al, 1987(Pitman et al, , 1990.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of response elements in the self-mutilation scripts administered to nonmutilators did not appear to alter arousal levels in either direction, despite suggestions that response elements enhance the psychophysiological arousal to imagery (Hirota & Hirai, 1986;Lang et al, 1980). The research investigating the efficacy of response versus stimulus imagery has relied on imagery presented in a single block or script.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…He assumed that response-oriented subjects showed greater physiological activity during imagery than did stimulus-trained subjects. Evidence to support the hypothesis was found in some experiments (Dekker & Everaerd, 1988;Hirota & Hirai, 1986;Lang, 1979;Lang, Kozak, Miller, Levin, & McLean, 1980;Lang, Levin, Miller, & Kozak, 1983). For response propositions, however, those previous studies investigated only the effects of arousal-response-oriented training.…”
mentioning
confidence: 85%
“…In keeping with previous findings, fear scenes produced larger heart rate and skin conductance responses than did neutral scenes, and subjects who were instructed to focus directly on responses during the imagery scenes showed greater heart rate increases. Several other research groups have demonstrated that increased response processing during imagery, achieved either by manipulating imagery content or through explicit response training and instructions, enhances physiological responding (e.g., Carroll, Marzillier, & Merian, 1982;Hirota & Hirai, 1986). More recently, Zander and McNally (1988) attempted to introduce increasing amounts of information into imagery scripts for agoraphobics (i.e., fear scripts included stimulus content only; stimulus and response content; or stimulus, response, and meaning content).…”
Section: Other Fear Lmagery Researchmentioning
confidence: 99%